Implementation of the Learning Method of the Prophet Muhammad Saw at Islamic Boarding Schools - Khumaidi, Mohammad Wisnu; Maimun, Agus; Fadil, Fadil (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to describe and analyze the implementation of the Prophet Muhammad SAW's learning method at the Madarijul Ulum Islamic Boarding School, Bandar Lampung. This research uses a qualitative descriptive approach with a type of field research. Primary data was obtained through observation, in-depth interviews with teachers and students, and documentation of learning activities. Secondary data was obtained from literature studies in the form of books, journals, Qur'anic verses, and relevant hadiths. The data collection technique uses participatory observation, semi-structured interviews, and documentation, with data analysis techniques through data reduction, data presentation, and conclusion drawn. The results of the study show that the five learning methods of the Prophet SAW—lecture/muhadharah, halaqah/egalitarian, reward and punishment (targhib-tarhib), gradual, and stories with wisdom—have been applied in an integrated manner in the pesantren environment. Each method has a distinctive form of implementation and has a positive impact on the development of character, discipline, and understanding of students. This finding affirms that the learning methods of the Prophet SAW remain relevant in the context of contemporary education and can be used as a reference in building a holistic Islamic education system. This research also highlights the importance of integrating prophetic values in character education. Recommendations for further research are to expand the location and context of the study, as well as examine the integration of the Prophet SAW's learning methods with technology-based learning approaches to answer the challenges of the times.